2021
DOI: 10.1038/s41467-021-27036-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation activates the yeast small heat shock protein Hsp26 by weakening domain contacts in the oligomer ensemble

Abstract: Hsp26 is a small heat shock protein (sHsp) from S. cerevisiae. Its chaperone activity is activated by oligomer dissociation at heat shock temperatures. Hsp26 contains 9 phosphorylation sites in different structural elements. Our analysis of phospho-mimetic mutations shows that phosphorylation activates Hsp26 at permissive temperatures. The cryo-EM structure of the Hsp26 40mer revealed contacts between the conserved core domain of Hsp26 and the so-called thermosensor domain in the N-terminal part of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 96 publications
4
14
0
Order By: Relevance
“…This could be due to the increased activity of smaller oligomeric species having a higher number of accessible binding sites per unit compared to the larger oligomers. This view is consistent with the observation made by Mühlhofer et al [12]. Alternately, it is plausible that smaller oligomers have activated chaperone sites that are otherwise constrained by specific sequences in the NTD, as discussed earlier with αB∆54-61 that showed increased chaperone activity compared to αB-WT [8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could be due to the increased activity of smaller oligomeric species having a higher number of accessible binding sites per unit compared to the larger oligomers. This view is consistent with the observation made by Mühlhofer et al [12]. Alternately, it is plausible that smaller oligomers have activated chaperone sites that are otherwise constrained by specific sequences in the NTD, as discussed earlier with αB∆54-61 that showed increased chaperone activity compared to αB-WT [8].…”
Section: Discussionsupporting
confidence: 91%
“…Further incubation of the protein with trypsin resulted in the complete hydrolysis of the protein at 30 min (data not shown). Comparing the mass spec data of trypsin-cleaved peptides generated from αB-WT and αB∆21-28, ∆54-61 at ten mins showed that 11 Arg-Arg 12 , 69 Arg-Leu 70 , 92 Lys-Val 93 , 120 Arg-Lys 121 , 123 Arg-Ile 124 , and 149 Arg-Lys 150 are the additional sites that became susceptible for trypsin action in the double mutant (Figure 5B; the targets for trypsin cleavage in the double mutant (green arrow) is shown corresponding to positions in the wild-type protein). The mass spectrometric results also indicated that the relative susceptibility of various cleavage sites varied.…”
Section: αB∆21-28 ∆54-61 Is More Susceptible To Cleavage By Trypsin T...mentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are stored in an inactive form as high-order oligomers, and their activation involves phosphorylation, especially in the NTR, that drives disassembly of sHSP into smaller complexes. For instance, several phosphorylation sites on Hsp26 were found to activate chaperon activity by weakening interactions within the oligomers (Mühlhofer et al, 2021). The phosphorylation of S223 on Hsp42 has been previously detected by mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical changes at any single site from mutation, modification, or damage are expected to affect the entire network. Consistent with this idea, phosphorylation of yeast Hsp26 ACD affects availability of its NTR for client interactions (Mühlhofer et al, 2021). Identification of NTR-to-ACD and NTR-to-NTR interactions and experimental approaches that can detect these provide a way to understand the effects of such mutations on sHSP structure and function.…”
Section: Ideas and Speculationmentioning
confidence: 85%